Detection of Ischemic Episodes Based on Two Consecutive Declines in the JT/ST Algebraic Relationship - Vaiva Šiaučiūnaitė; Alfonsas Vainoras; Zenonas Navickas; Minvydas Ragulskis (Applied Sciences, 2021)
The main objective of this paper is to explore if the JT/ST algebraic relationship could be helpful for the identification of ischemic changes in the human cardiovascular system. The suggested visualization technique highlights the specifics of complex dynamical processes in the self-organization of the heart system during the load and recovery processes. It is demonstrated that the nonlinear algebraic relationship between the duration of the JT interval and the ST amplitude can be beneficial for a deeper interpretation of dynamical processes in the human cardiovascular system. The JT/ST relationship is used for the identification of the ischemic changes and for the characterization of individual performance of the person during the load and recovery processes.